Chapter Слушая Сад: переосмысление звуковых аспектов чеховской пьесы на примере японской и итальянской постановок - Murata, Shin’ichi (Firenze University Press, 2024)
Listening to The Orchard: Rethinking the Sound Aspect of Chekhov’s Play in Japanese and Italian Productions. The best dramatists write plays in such a way that the performance can realize the deep meaning of the sound aspect of the original text. In the belief of theatrical art, sound is much closer to tangibility than appearance. Using The Cherry Orchard by A.P. Chekhov as an example, the article examines the role and significance of distinct types of “live sound” that figure out the theatricality of a literary text and its concept. For comparative analysis, well-known Japanese and Italian performances based on The Cherry Orchard in the second half of the 20th century and early 21st centuries are compared.